Oxidative stress status in nutritionally stunted children - Gamal Samy Aly; Ashraf Hamed Shaalan; May Kamel Mattar; Hanaa Hamdi Ahmed; Moushira Erfan Zaki; Hanaa Reyad Abdallah (SpringerOpen, 2014)
Introduction: Oxidative stress is the imbalance between pro-oxidants and antioxidants resulting in irreversible cell damage. Objective: To assess the oxidative stress status in a sample of Egyptian malnourished stunted children and investigate the relations between oxidative stress markers and anthropometric measurements. Patients and methods: This cross sectional descriptive analytical study was carried out on 50 malnourished stunted children (28 males and 22 females), aged from 6-9 years and 50 healthy age and sex-matched controls. Blood oxidative stress biomarkers including catalase (CAT), superoxide dismutase (SOD) malondialdehyde (MDA), plasma glutathione (GSH), total plasma proteins, total anti-oxidant capacity (TAC), copper (Cu), zinc (Zn), and vitamin C were measured in patients and controls. Socio-economic status was assessed for patients. Body weight and height were measured and body mass index (BMI) was calculated. Patients were classified according to their height for age Z-scores (HAZ) into moderate and severe stunted. Results: Nutritionally stunted children showed significantly lower levels of the blood oxidative stress biomarkers including, CAT, SOD, plasma GSH, total plasma proteins, Cu, Zn and vitamin C and significantly higher levels of MDA compared with controls (p < 0.001). There was significant difference in plasma levels of Vitamin C and Zn between patients with different social levels. No significant relationships were found between the degree of stunting and oxidative markers. Conclusions: Nutritionally stunted children had an increased oxidative stress and decreased antioxidant defense system compared with healthy controls. Oxidative stress, malnutrition and low social level might play an important role in the pathogenesis of stunting.